TRAIL BLAZER. (Economist, 1998)
A profile of Katrina Garnett, Founder, President and chief executive officer (CEO) of CrossWorlds Software Inc. is presented. Garnett was born in Australia's Gold Coast. She spent 10 years on the firing line at Oracle and Sybase. She started Garnett Foundation to encourage girls to pursue technical careers. It is stated that her mission is to build software applications that unite the operations of global enterprises.